Pengendalian Internal Manajemen pada PT. Citra Mandiri Distribusindo melalui penerapan Sistem Microsoft Access untuk Meningkatkan Efisiensi Operasional Perusahaan - Itan, Iskandar; Sylvia, Sylvia (Universitas Pahlawan Tuanku Tambusai, 2024)
PT Citra Mandiri Distribusindo is a leading distribution company that faces various challenges in management control, such as difficulties in monitoring employee performance, managing stock and inventory, and managing customer credit. These challenges lead to operational inefficiencies that result in decreased productivity and customer satisfaction. This research aims to develop an effective management control system using Microsoft Access to improve the company's operational efficiency and effectiveness. The research method involved several stages, including requirements analysis, system design, implementation, and evaluation. The creation of an integrated database included tables for employee data, inventory, financial reports, and credit policies. The employee performance evaluation system was designed to facilitate periodic appraisals that are objective, data-driven, and transparent. Real-time stock management enables the company to perform periodic inventory counts, apply demand forecasting techniques, and control inventory more accurately using Microsoft Access. The reporting and data analysis system helps identify trends and patterns that affect the company's performance, while the customer credit policy module covers payment monitoring and credit risk handling.